2021
DOI: 10.1002/prp2.738
|View full text |Cite
|
Sign up to set email alerts
|

Increase in the risk of clopidogrel resistance and consequent TIMI flow impairment by DNA hypomethylation of CYP2C19 gene in STEMI patients undergoing primary percutaneous coronary intervention (PPCI)

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 32 publications
(61 reference statements)
1
11
0
Order By: Relevance
“…Yang et al [25] compared the whole genomic methylation patterns of blood samples and found that the CR and non-CR showed significantly different DNA methylation at 7,098 sites, with 979 sites showing hypermethylation and 6,119 sites showing hypomethylation. Sukmawan et al [26] investigated the role of CYP2C19 gene DNA methylation for CR in ST-elevation MI patients undergoing primary percutaneous coronary intervention and found that DNA methylation level percentage was significantly lower in the CR group than in clopidogrel responder group. Su et al [14] found the aberrant methylation DNA methylation of CR patients in the ABCB1, P2Y12 [15], and PON1 genes [12].…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al [25] compared the whole genomic methylation patterns of blood samples and found that the CR and non-CR showed significantly different DNA methylation at 7,098 sites, with 979 sites showing hypermethylation and 6,119 sites showing hypomethylation. Sukmawan et al [26] investigated the role of CYP2C19 gene DNA methylation for CR in ST-elevation MI patients undergoing primary percutaneous coronary intervention and found that DNA methylation level percentage was significantly lower in the CR group than in clopidogrel responder group. Su et al [14] found the aberrant methylation DNA methylation of CR patients in the ABCB1, P2Y12 [15], and PON1 genes [12].…”
Section: Discussionmentioning
confidence: 99%
“…50 Moreover, the diabetic state also affects profoundly the epigenetic landscape, possibly altering the expression of genes whose products alter clopidogrel pharmacokinetics and pharmacodynamics. 19,20,51 Diabetics are, therefore, a population of patients at high risk of recurrent thrombotic events even under clopidogrel therapy. 32,33,52,53 Type 2 diabetes, especially the insulin-dependent type, was strongly associated with disease relapse in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Physiologically, patients with type 2 diabetes mellitus are characterized by a prothrombotic status favored by resistance to antithrombotic physiological signals, shear‐induced aggregation, nonenzymatic glycation of platelet glycoproteins, changes in the structure and conformation of platelets, increased oxidative stress, and increased platelet turnover 50 . Moreover, the diabetic state also affects profoundly the epigenetic landscape, possibly altering the expression of genes whose products alter clopidogrel pharmacokinetics and pharmacodynamics 19,20,51 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations